1999
DOI: 10.1164/ajrccm.159.5.9809025
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Prevents Respiratory Depression in Obesity

Abstract: Human obesity leads to an increase in respiratory demands. As obesity becomes more pronounced some individuals are unable to compensate, leading to elevated arterial carbon dioxide levels (PaCO2), alveolar hypoventilation, and increased cardiorespiratory morbidity and mortality (Pickwickian syndrome). The mechanisms that link obesity and hypoventilation are unknown, but thought to involve depression of central respiratory control mechanisms. Here we report that obese C57BL/6J-Lepob mice, which lack circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
256
2
14

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(283 citation statements)
references
References 26 publications
11
256
2
14
Order By: Relevance
“…For example, leptin has been postulated to mediate OSA susceptibility via effects on ventilatory drive. 21 Variability in adipokine levels has been found to closely aggregate within families, and linkage studies have identified potential genetic risk factors regulating the levels of each of the adipokines assessed in this study. [22][23][24] The significant estimates of heritability we calculated for levels of leptin, adiponectin and resistin also support an important genetic basis for these adipokines.…”
Section: Discussionmentioning
confidence: 80%
“…For example, leptin has been postulated to mediate OSA susceptibility via effects on ventilatory drive. 21 Variability in adipokine levels has been found to closely aggregate within families, and linkage studies have identified potential genetic risk factors regulating the levels of each of the adipokines assessed in this study. [22][23][24] The significant estimates of heritability we calculated for levels of leptin, adiponectin and resistin also support an important genetic basis for these adipokines.…”
Section: Discussionmentioning
confidence: 80%
“…With respect to mice that were leptin receptor deficient due to genetic mutation, Tsuchiya et al (1999) reported that the rate of tracheal epithelial cell proliferation was only one-quarter (P , 0.01) that of their unaffected littermates, illustrating a potentially important supplementary role for leptin in pulmonary development. Other studies further suggest a significant impact of leptin on general pulmonary health in rodents (O'Donnell et al 1999), as well as on specific respiratory disorders in humans (O'Donnell et al 2000). Intriguingly, obesity-related respiratory anomalies are characteristically exacerbated in males (Kapsimalis & Kryger 2002), perhaps reflecting again the gender dichotomy that is typical with respect to circulating leptin concentrations (Casabiell et al 2001).…”
Section: Discussionmentioning
confidence: 94%
“…In the ob/ob mouse, respiratory anomalies that are common with the obese phenotype (tachypnea, decreased lung compliance and aberrant respiratory muscle adaptations) were attenuated following prolonged leptin administration (Tankersley et al 1998). Similarly, in wild-type mice that were obese merely as a consequence of their high-fat diet, respiratory depression was alleviated by leptin treatment (O'Donnell et al 1999).…”
Section: Introductionmentioning
confidence: 97%
“…A central role of leptin as a neurohumoral modulator of central respiratory mechanisms and lung function has furthermore been established in animal models [35].…”
Section: Discussionmentioning
confidence: 99%